I disastri della guerra. Perché salvare la cultura? (Gruppo editoriale Tab Srl, 2025)
War – any war, of any kind – is a disaster of immense proportions, both for the loss of human lives and for the annihilation of a people’s culture and history, of an entire civilization. For these reasons, the international conference, the proceedings of which are published in this volume, was titled The Disasters of War. Why Save Culture? A provocative title meant to draw the attention of civil society, to take stock of the global situation, and above all, to propose innovative solutions for the preventive protection of the world’s cultural heritage – historical, artistic, archaeological, and monumental. The conference was conceived and promoted by SIPBC, the Italian Society for the Protection of Cultural Heritage, in collaboration with the University of Bologna.